Private information, yield volatility, and interaction between groups of investors: Case of Indonesia government bond market - Buddi Wibowo (University of Merdeka Malang, 2019)
Relation of private information and yield volatility in the relatively low liquid markets such as the Indonesia government bond market is one of the recent important research topics in finance. Because private information accumulation mastery affects interaction patterns between dealers dan their customers, it is urgent to identify this price mechanism in the government bond market, especially in a low liquid market in which small trading volume may create serious yield volatility. If there is a substantial disagreement on bond fair value because of distinct private information quality between each of those groups of investors' success to accumulate it, bond price will fluctuate wildly. This paper study the dealer and customer order flow interaction to identify which side that have greater impact on yield volatility. The results show that from the two layers of order flow, disagreement between dealers and customers is slightly in a short-term and medium-term bond so their volatility is relatively low. But for a long-term bond, disagreement is substantial and creates high yield volatility. Different trading platforms and strategies between dealers and customers play an important role in creating high yield fluctuations.JEL Classification: G12, G14, G11DOI: https://doi.org/10.26905/jkdp.v23i2.2823